The effects of practicing communicative approach in the teaching of speaking skill - Noraien Mansor Dr. 1960-; Mohd. Jalani Hasan (Penerbit UMT, Universiti Malaysia Terengganu, 2014)
This monograph will help the reader to have a clear view on what the authors had done, the implications towards the body of knowledge and the suggestions to upgrade the standard of teaching speaking skills among students